STUDI ANALISA SISTEM INSTALASI PENGOLAHAN AIR LIMBAH RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Agus Catur Pramite; Muhamad Yamin; Kusmianti Kusmianti (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The purpose of this study was to determine the effectiveness value of the Wastewater Treatment Plant in the Mataram City Regional General Hospital (RSUD). This study used 2 sampling locations consisting of the tub before the process (Inlet) and the tub after the process (Outlet). There are 5 parameters observed consisting of Total Suspended Solid (TSS), Biological Oxygen Demand (BOD), Chemycal Oxygen Demand (COD), Oil and fat, and pH (Degree of Acidity). Samples were tested in the laboratory and then analyzed. The results showed 1) Total Suspended Solids (TSS) with a standard standard of 30 mg / l. After processing, it was obtained 18.0 mg / l. 2) Biologycal Oxygen Demand (BOD) with a standard standard of 50 mg / l. After the processing process is carried out, it is obtained 1.47 mg / l. 3) Chemycal Oxygen Demand (COD) with a standard standard of 80 mg / l. After processing, it is obtained 28.9 mg / l. 4) Oils & fats with a standard standard of 10 mg / l. After the processing is carried out, it is obtained <1.00 mg / l. 5) pH (degree of acidity) with a standard of 10. After the processing is carried out, it is obtained 7.72.